2018
DOI: 10.1051/epjconf/201817609011
|View full text |Cite
|
Sign up to set email alerts
|

Saver.net lidar network in southern South America

Abstract: The South American Environmental Risk Management Network (SAVER-Net) is an instrumentation network, mainly composed by lidars, to provide real-time information for atmospheric hazards and risk management purposes in South America. This lidar network have been developed since 2012 and all its sampling points are expected to be fully implemented by 2017. This paper describes the network’s status and configuration, the data acquisition and processing scheme (protocols and data levels), as well as some aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
1
8
0
2
Order By: Relevance
“…These results are consistent with previous studies indicating that the volcanic plume is dominated by larger particles near the source (Hobbs et al, 1982;Rose et al, 2000;Watson and Oppenheimer, 2000;Webster et al, 2012). Rose et al (1982) showed that this phenomenon could be explained by competing mechanisms involving the adsorption of smaller particles by ash. As reported by Sparks et al (1997), aggregation processes are more important near the source.…”
Section: Gobabebsupporting
confidence: 93%
“…These results are consistent with previous studies indicating that the volcanic plume is dominated by larger particles near the source (Hobbs et al, 1982;Rose et al, 2000;Watson and Oppenheimer, 2000;Webster et al, 2012). Rose et al (1982) showed that this phenomenon could be explained by competing mechanisms involving the adsorption of smaller particles by ash. As reported by Sparks et al (1997), aggregation processes are more important near the source.…”
Section: Gobabebsupporting
confidence: 93%
“…The CALIPSO CALIOP 5 km aerosol profile product version 4.1 is available under https://doi.org/10.5067/CALIOP/CALIPSO/LID_L2_05kmAPro-Standard- V4-10 (Vaughan et al, 2016). Backward trajectories' analysis was supported by air mass transport computation with the NOAA (National Oceanic and Atmospheric Administration) HYSPLIT model (HYSPLIT, 2018) using GDAS meteorological data (Stein et al, 2015;Rolph et al, 2017). AERONET Sun photometer AOT data were downloaded from the AERONET web page (http://aeronet.gsfc.nasa.gov/, last access: 8 May 2019).…”
mentioning
confidence: 99%
“…Measurements from the lidar instrument installed at CITEDEF were analyzed to determine the height of the aerosol layers. The normalized aerosol backscattering coefficient was calculated at 532 nm [47][48][49]. This system allows measuring the atmosphere's profiles from a few meters to several kilometers, exceeding the tropopause height up to the lower stratosphere.…”
Section: Detection Of Biomass Burning Eventsmentioning
confidence: 99%